Gene space completeness in complex plant genomes. (April 2019) - Van Bel, Michiel; Bucchini, François; Vandepoele, Klaas
Highlights: Historical perspective shows an increase in annotated genome complexity in plants. Gene completeness of different gene types is a multifaceted problem. Genome completeness generally improves over multiple consecutive annotations. Partial gene models continue to be a challenge even for model organisms. Abstract : Genome annotations offer ample opportunities to study gene functions, biochemical and regulatory pathways, or quantitative trait loci in plants. Determining the quality and completeness of a genome annotation, and maintaining the balance between them, are major challenges, even for genomes of well-studied model organisms. In this review, we present a historical overview of the complexity in different plant genomes and discuss the hurdles and possible solutions in obtaining a complete and high-quality genome annotation. We illustrate there is no clear-cut answer to solve these challenges for different gene types, but provide tips on guiding the iterative process of generating a superior genome annotation, which is a moving target as our knowledge about plant genomics increases and additional data sources become available.